Upaya Pengembangan dan Implementasi Pariwisata Berkelanjutan di Desa Wisata Serangan Bali - Zaenab Nur Azkia; Nirwana Noer Klarisa; Dinda Wulandari; Naomi Viorella Yohana Silalahi; Fauzan Ali Ikhsan (Universitas Sebelas Maret Surakarta, 2025)
Development Efforts and Implementation of Sustainable Tourism in Serangan Bali Tourism VillageThe Serangan Tourism Village requires strengthening a sustainable tourism strategy to optimize the strategic potential of the coastal area which includes 204.37 hectares of RTH-mangrove, religious tourism, and the local creative economy. The research uses a descriptive qualitative approach through field observations, interviews with managers, Pokdarwis, business actors, the community, and tourists, as well as documentation to analyze the implementation of the three pillars of sustainability. The findings show: environmental aspects are managed through mangrove conservation and Angen Bali's recycling program; the economic aspect is strengthened by the DEWI SITA Program with the development of seafood culinary and local handicrafts; The socio-cultural aspect is maintained through the preservation of Sakenan Temple and the active participation of the younger generation. The research resulted in the concept of an integrated area architecture master plan including conservation zoning, structured creative economy centers, and community-based management systems as a replica model for sustainable tourism village development in Indonesia.